Development of the UI/UX for the Madrasah Adaptation E-Module Using the Design Thinking Method - Stephanus Widjaja; Adityo Putro Wicaksono; Abdul Rozacky; Farrell Feodora Nikolaus Putra; Chanif Musoffa (Universitas Wahid Hasyim, 2026)
Technological developments have brought major changes in the world of education, especially in the development of digital learning media. This study aims to design a user interface and user experience on a mobile-based habituation e-module application at MA Taqwiyatul Wathon as a solution to the limitations of physical modules that have been used in students' daily habituation activities. The method used is Design Thinking which consists of five stages, namely Empathize, Define, Ideate, Prototype, and Test. The research process involved three groups of users, namely students, teachers, and admins through observation, interviews, and direct testing of the High-Fidelity Prototype (Hi-fi) using the In-Person Usability Testing method based on a Likert scale (1–5). The test results showed a Usability Score of 91.7 for students, 97.2 for teachers, and 90 for admins, with the category